Establishment and Development of Ningxia Hui Autonomous Region of People’s Republic of China (1949—1979) - A. G. Nesterov; E. E. Khanina (Научный диалог, 2022)
The article is devoted to one of the autonomous regions of the People’s Republic of China — the Ningxia Hui Autonomous Region (NHAR). The historical events associated with the territory of modern NHAR, the features of the development of Islam in China and the formation of the Hui ethnic group is showed in the article. As a result of the study, it was revealed that the creation of the NHAR was due to the ideological concepts of national development laid down in the 1954 Constitution of the People's Republic of China. Based on documents published in China in Chinese, it is proved that the creation of the NHAR played a significant role in the ethnic development of the Hui people. It was revealed that the political changes that took place in the PRC in 1958-1976 and associated with the policy of the “Three Red Banners” and the “Great Proletarian Cultural Revolution” caused significant damage both to the economy of the NHAR and to ethnic stability in the considered region of China. The implementation of political campaigns of this period even led to clashes on confessional and ethnic grounds, which required the use of armed force to suppress them. As a result of the study, it was revealed that the situation in the NHAR began to stabilize and change only after the death of Mao Zedong and the beginning of Deng Xiaoping's reforms in 1979.